2013
DOI: 10.1590/s2176-94512013000300008
|View full text |Cite
|
Sign up to set email alerts
|

Transversal changes in dental arches from non-extraction treatment with self ligating brackets

Abstract: The results indicated that the majority of transverse changes occurred at the premolar areas, both the first and the second, as well as on the upper and lower dental arches. The intercanine distance increased 0.75 mm, on average, in the upper arch and 1.96 mm in the lower arch. The molars also demonstrated a tendency towards an increase in their transverse dimension, however, at a lower intensity comparing to premolars. All measurements presented statistically significant differences with the exception of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
1
13
2
2
Order By: Relevance
“…Insufficient occlusal contacts, which can limit dental tipping unlike in the posterior teeth, could be the reason for the shift of this protrusion through the anterior region. 22 In our study, the mean values for the intercanine arch perimeter were higher in the CuNiTi group than in the NiTi group ( p < 0.01) from the second week. The covariates were adjusted for initial values of all examined parameters.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Insufficient occlusal contacts, which can limit dental tipping unlike in the posterior teeth, could be the reason for the shift of this protrusion through the anterior region. 22 In our study, the mean values for the intercanine arch perimeter were higher in the CuNiTi group than in the NiTi group ( p < 0.01) from the second week. The covariates were adjusted for initial values of all examined parameters.…”
Section: Discussioncontrasting
confidence: 38%
“… 24 Some studies have suggested an increase in arch perimeter after nonextraction orthodontic treatment in patients with Class I malocclusion. 22 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More expansion in the premolars region can be because of lip bumper effect which minimizes the proclination of anterior teeth and allow more expansion in posterior region. Previous study also showed majority of transverse changes in the premolar areas in both upper and lower arches, with less expansion in the canine and molar region (16,17). While assessing maxillary arch depth, the study showed (Table 1) a decrease in arch depth which can be because of more of transverse expansion, which created space and helped in unraveling of crowding in upper anteriors and less proclination.…”
Section: Discussionmentioning
confidence: 71%
“…The inter-molar distance also showed a widening but to a lesser degree. All the transverse measurements proved to be equally significant with the exception of the width between the maxillary second molars 28 .…”
Section: Are Self-ligating Brackets An Advantageous Alternative For Nmentioning
confidence: 88%